(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: Structuralism and Post-Structuralism are two of the most influential theoretical movements of the 20th century, fundamentally shaping contemporary thought in fields such as linguistics, philosophy, anthropology, and literary theory. Structuralism emerged in the early 20th century, grounded in the belief that human culture, language, and social practices are governed by underlying structures that are universal and objective. Led by figures like Ferdinand de Saussure and Claude Lévi-Strauss, Structuralism sought to uncover these deep structures, which were thought to function independently of individual human experiences and historical contexts. In contrast, Post-Structuralism emerged as a critique of Structuralism in the 1960s and 1970s, challenging the idea that meaning could be stable or universal. Prominent thinkers like Jacques Derrida, Michel Foucault, and Roland Barthes argued that meaning is not fixed, but instead is fluid, subjective, and contingent upon context. Post-Structuralism rejects the notion of stable structures, highlighting the role of power, history, and culture in shaping meaning, and emphasizing the multiplicity and instability of interpretations.